Penerbitan Izin PT. RAPP di Pulau Padang (Analisis Kebijakan dan Sosiologi Konflik) - Boy Jerry Even Sembiring (Jurnal Selat, 2015)
Permission publication is state’s authority to allow someone or a group of people, or law institution to commit a certain activity. Eventhought that is an authority in state’s authority, its publication still must be done selectively by noticing formal juridicial aspect (term of rule of legislation) sociology, or even ecology. however, in its practice, it’s often found the published permission through the decision or other instruments which disobey the term of rules of legislation, which cause social and ecology impact. The study in this transcription relates to the IUPHHKHT publication problem to PT. RAPP in Padang island. the permission publication by forestry ministry causes the complex problematic in Padang island appeans. the publication of degree. 327 in 2009 and degree 180 in 2013 have contradicted several rules of legislation, especially the one related to coastal and isles territory management, and internal peat area utilization. The revision of degree. 327 which is based on mediation term’s recommendation is a disablement, because the state as one of the cause of conflict even tried to mediate and in fact, the mediation team is also failed to gather the people and the company in a discussion. The publication of degree 180 as the transformation’s policy also disobeyed the recommendation they selected. The existence of conflict, related to the persistence of people management territory overlapping with concession; the inhuman compensation payment which is far from the land price’s normal standard; environmental demage conflict and demand for woods; and horizontal conflict between societies. the overall conflict those still exist indicate the state failed and neglected the fulfillment and protection of Padang Island societies right as citizens. Key words : Permission, Policy, Sociology of Conflict.